CURRICULUM DESIGN OF VIRTUAL SIMULATION EXPERIMENT OF THERMISTOR TEMPERATURE MEASUREMENT CHARACTERISTICS BASED ON EDUCATIONAL PSYCHOLOGY - Fei, Teng; Zhu, Cheng; Zhang, Liyi; Liu, Xiaopei; Zhang, Yong; Li, Hui (The international journal of neuropsychopharmacology, 2022)
Abstract Background In order to meet the social demand for applied and innovative talents and meet the “advanced, innovative and challenging” university education standard of the Ministry of education, colleges and universities continue to explore new training modes and teaching forms. High quality experimental teaching plays an important role in cultivating students' practical ability and innovative ability. Thermistor is an important category of sensors. Through experimental operation, students can effectively understand and master its physical structure, working principle and application characteristics. Subject and Method In order to overcome the disadvantage of limited resources of traditional thermistor equipment, the design of this virtual simulation experiment follows the principle of “maximum authenticity, combination of virtualization and authenticity”. From the perspective of educational psychology, taking the temperature control link of central heating and air supply system as the background, the experimental steps are designed around the thermistor, and the students are guided to carry out the temperature measurement characteristic experiment of thermistor in combination with the knowledge points such as PID control algorithm and single chip microcomputer data processing. Each step of the experiment is designed to test students' mastery of corresponding knowledge and skills. In addition, by scientifically simplifying and virtualizing each link of the gas supply system, on the premise of ensuring the integrity of the process and the authenticity of the experience, the experimental steps outside the scope of the “sensor” course are still “achievable” for the experimenter. Form the whole process of communication before, during and after the experiment to effectively explain knowledge to students. Before the experiment, students should learn the theoretical knowledge, precautions and operation skills required by the experiment; During the experiment, students should understand information, make plans and collect data; After the experiment, students and teachers make full use of the scattered time segments to communicate on the problems in the experiment. Results Students can query the technical data, choose the design scheme, observe the experimental results, deepen the understanding of thermistor knowledge, improve the engineering practice ability, and get rid of the limitations of time and space in the process of repeatedly “making mistakes” and “correcting mistakes”. The project can completely copy a system through virtual instrument. No physical heat source, no equipment performance degradation, no special safety control requirements, and no restrictions on equipment resources, site and time. It can effectively solve the problems that thermistor is easy to cause performance attenuation, precision decline and affect the effect of experimental teaching. Conclusion After long-term use, the experimental design will not lead to the decline of component performance and material consumption. The experimenter can remotely complete the experimental operation anytime and anywhere through the computer connected to the network, so as to obtain the sensory experience close to the actual operation of the experimental equipment. In short, we should carry out relevant combination of industry and education according to our own advantages and characteristics. Make clear the goal of motivation by example, and regularly hold activities such as successful model sharing, experience introduction and project display, so as to set a successful example for positive emotions, clarify the specific objectives of the activities, form a strong psychological momentum, stimulate internal potential and help the realization of positive behavior. We should strengthen professional guidance, give full play to the concentration of professionals, high intelligence, professional knowledge in business fields, and give full play to the advantages of talents and intelligence. We can organize experts and scholars to establish a professional bid winning guidance team, give full play to the business projects of experts and scholars in their respective fields, and carry out scientific research on relevant projects. Acknowledgements Supported by a project grant from Ministry of Education Collaborative Education Project (202102343015).